Information-Mental and Socio-Evolutionary Contexts of the Dynamics of War and Peace - Nikolai S. Rozov (Гуманитарный вектор)
The fi rst decades of the XXI century are marked by processes of turbulence, multiple tensions and dramatic events. In this context, the issues of geopolitics, war and peace play a particularly signifi cant role. On the basis of synthesis and clarifi cation of fundamental concepts and principles of social anthropology, psychology, sociology, political sciences, we present a holistic dynamic model of factors of emergence, escalation and termination of wars, and their macro-social consequences. Taking into account these provisions, we provide theoretical answers to fundamental questions about the causes of war. The study is based on the following methods: analysis and synthesis, conceptual study of basic concepts from different spheres of social and humanitarian knowledge, formulation and substantiation of fundamental principles of war and peace dynamics, theoretical comprehension of heterogeneous empirical generalizations. Wars are always related to concerns and social universals: violence/ security, power-power, resources-wealth, and prestige-legitimacy. At the same time, wars are triply related to information, cognitive processes, and, in the modern world, new media and propaganda technologies. Powerfuldecisions on the use of military force, leading to wars, are made on the basis of “fast” or “slow” thinking according to Kahneman. The course of war itself, apart from the “material” component of mobilization and mutual destruction, always includes a struggle of wills – attempts by each side to impose a ritual scenario of the inevitability of its defeat on the enemy. The outcome of the war is always the subject of a struggle of interpretations and narratives on the part of the strongest post-war political-ideological forces. The specifi c role of war in the co-evolution of social, mental and techno-natural orders is presented with these provisions in mind. The constructed conceptual apparatus, formulated principles and ideas of the holistic dynamic model of the emergence, course and termination of wars are intended for deeper theoretical and empirical research in this important and relevant subject area. In addition, they should contribute to the analysis, design and implementation of such objective and subjective conditions that will not ensure the proverbial “eternal peace”, but will minimize the factors of new wars.